Nilai-Nilai Pendidikan Islam Dalam Serial Animasi Nussa (Episode Compilation Vol.12) - Fadillah, Mutiah; Al-Ghifari, Muh.; Lessy, Zulkifli (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
The background of the problem in this research means that the number of spectacles presented in global Indonesian cinema is so diverse. Nowadays, all people are able to access various things. The existence of technological advances, has the potential to change the human personality itself, for example, such as the decline in morals possessed by children both in the scope of the family and society more or less. This research aims to analyze the values of Islamic education contained in the animated series Nussa Episode Compilation Vol. 12. The result of this research is expected to increase knowledge about Islamic religious education and how to educate children from an early age. This research means qualitative research with the type of library study (library reasearch). The approach used in this research is a semiotic approach using attention, understanding, and analyzing the symbols contained in the film. the results of this study show: The values instilled in the animated series Nussa episode compilation vol.12 are: the value of faith, the value of sharia, and the value of morals.